IDENTIFIKASI PENGEMBANGAN PARIWISATA KOTA BLITAR - Afandi, Aang (Proceeding SENDI_U, 2015)
Economic structure of Blitar Municipality supported by: (1) trade, hotels and restaurants (32.28%), (2) servicessector (19.57%), (3) the financial sector, leasing and business services (12.79%) and (4) processing industrysector (11.39%). The fourth sector is exactly what the biggest contribution in Blitar, based on the data in 2013.One major note, in Blitar, there is the tomb of one of the Proclaimers namely Ir. Sukarno, who makes Blitar ashistorical sights become a visiting various communities to Blitar. With this background, the Blitar has thepotential to develop tourism that encourages and complements the historical attractions Blitar. The purpose ofthis study is to identify the potential and opportunities that enable can be developed in the city of Blitar as longas this is a tourist town history. This research method is a rapid method of quick research, is one of the researchmethods used to shorten the time in order to obtain initial results more quickly, as the beginning of a studyinformation. The goal is to provide rapid and incisive analysis of trends and developments and to investigate arelevance to the practical world. With desk approach utilizing secondary data analysis with relevant andavailable. The results show that the potential and opportunities that enable tourism developed in Blitar is tourismthat supports the main tourist destinations with historical tours available resource utilization.Keywords: tourism, historical tourism, Blitar.